IMPLEMENTASI ETIKA PROFESI DAN LOCUS OF CONTROL TERHADAP KINERJA AUDITOR - JAZADI, FURQAN RAMADHAN (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study is to provide an overview of the application of professional ethics and locus of control to auditor performance either by internal auditors within a company or auditors at a Public Accounting Firm. This research uses the Systematic literature Review (SLR) method. This method is carried out by reviewing several national and international standard journals. The results showed that the quality of auditor performance audit results is dominantly influenced by several situational factors and characteristics of an auditor, for example professional ethics and locus of control that exist for all auditors. This internal locus of control has a positive effect on audit quality, the more internal the locus of control, the higher the audit quality. The external locus of control has a negative effect on audit quality and audit quality decreases. Certified auditors who have good professional ethics will have a positive impact on the auditor's performance. The better the professional ethics of an auditor, the better the auditor's performance will be. An auditor's internal locus of control will behave ethically compared to the auditor's external locus of control which tends to behave unethically.